Novel additions to Corynespora Gussow from India - VIVEK K. PAL, D.P. SINGH and D.K. AGARWAL, SHAMBHU KUMAR, RAGHVENDRA SINGH, (Indian Phytopathology, 2008)
This communication deals with the description, latin diagnosis and illustrations of three hitherto undescribed species of fungus genus Corynespora Gussow viz., C. brevispora sp. nov., C. crotonicola sp. nov., and C. glochidicola sp. novo collected on the dead petiole of Carica papaya (Caricaceae), living leaves of Croton bonplandianum (Euphorbiaceae) and Glochidion lanceolarum (Euphorbiaceae) respectively, from North-eastern Uttar Pradesh, India.